1997
DOI: 10.2118/35698-pa
|View full text |Cite
|
Sign up to set email alerts
|

Kuparuk Large-Scale Enhanced Oil Recovery Project

Abstract: The Kuparuk River oil field has had a "miscible" water-alternatinggas (MWAG) enhanced-oil-recovery (EOR) pilot in place since 1988. This original pilot was implemented on two drillsites previously on waterflood. The pilot was expanded to a third drillsite in 1993 to test the MWAG process in an area previously flooded by an "immiscible" water-alternating-gas (IWAG) recovery technique. Large-scale application of MWAG at Kuparuk is in progress, with a project that will more than triple current MWAG injection. Ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Ultimate EOR from the pilot area is estimated to be 7 -10% OIIP. Field-wide implementation followed in 1996 (Hoolahan et al, 1997). Subsequent study work assessed the value of following IWAG with MWAG.…”
Section: Kuparukmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimate EOR from the pilot area is estimated to be 7 -10% OIIP. Field-wide implementation followed in 1996 (Hoolahan et al, 1997). Subsequent study work assessed the value of following IWAG with MWAG.…”
Section: Kuparukmentioning
confidence: 99%
“…Incremental recovery is expected to be 200 mmstb, based on injection of 1 Tscf of MI, making Kuparuk one of the world's largest miscible gas floods. Conventional WAG (WAG ratio = 1:1, MI slug = 30% HCPV) is used and the EOR from individual patterns is expected to be 4% -10% OIIP (Hoolahan et al, 1997). Only half the Kuparuk OIIP is currently subjected to the WAG EOR process; the potential for EOR expansion at Kuparuk is therefore significant.…”
Section: Kuparukmentioning
confidence: 99%
“…However, some field projects involving immiscible CO 2 or hydrocarbon flooding (e.g. Lick Creek, Kuparuk River, Forest Reserves, Brage and Gullfaks) showed that WAG could be applied in the immiscible mode also [3][4][5][6][7][8][9][10].…”
Section: Feasibility Studiesmentioning
confidence: 99%
“…The field was put on production in 1981, with a field-wide waterflood recovery development initiated in 1983. Recoverable reserves in the field are in excess of 0.32 × 10 9 m 3 [2 billion bbl] with the first billion barrels having been produced by May 26, 1993 3 .…”
Section: Introductionmentioning
confidence: 99%